2021
DOI: 10.1038/s41598-021-90492-0
|View full text |Cite
|
Sign up to set email alerts
|

Disseminated intravascular coagulation immediately after trauma predicts a poor prognosis in severely injured patients

Abstract: Trauma patients die from massive bleeding due to disseminated intravascular coagulation (DIC) with a fibrinolytic phenotype in the early phase, which transforms to DIC with a thrombotic phenotype in the late phase of trauma, contributing to the development of multiple organ dysfunction syndrome (MODS) and a consequently poor outcome. This is a sub-analysis of a multicenter prospective descriptive cross-sectional study on DIC to evaluate the effect of a DIC diagnosis on the survival probability and predictive p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 40 publications
1
12
0
Order By: Relevance
“…Table 1 shows that the low AT group had a higher proportion of elderly individuals and women. Previous studies have suggested that hypercoagulability in women after injury may be caused by the effects of estrogen (7,26,27). In addition, increased tissue factor expression, which activates extrinsic The SF levels on hospital arrival based on the general coagulofibrinolytic markers, including antithrombin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 1 shows that the low AT group had a higher proportion of elderly individuals and women. Previous studies have suggested that hypercoagulability in women after injury may be caused by the effects of estrogen (7,26,27). In addition, increased tissue factor expression, which activates extrinsic The SF levels on hospital arrival based on the general coagulofibrinolytic markers, including antithrombin.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, DAMPs induce neutrophil activation, followed by the release of neutrophil extracellular traps (NETs) that mainly comprise histones and promote further thrombin generation. These processes constitute the pathophysiology of disseminated intravascular coagulation (DIC), which is defined on the basis of dysregulated inflammatory coagulofibrinolytic responses to a traumatic insult (5,6) and can induce poor outcomes through the development of consumption coagulopathy and multiple organ dysfunction syndrome (MODS) (7). Another important factor in the pathophysiology of DIC is impaired anticoagulant mechanisms (2).…”
Section: Introductionmentioning
confidence: 99%
“…Third, medical students and medical staff from our hospital were recruited as healthy volunteers using a selection method employed in our previous studies: however, they were not age- or sex-matched to the patients. Fourth, we centrifuged collected blood samples at 4°C to avoid false high value of measurements in accordance with our previous studies ( 19 21 ). However, one-time centrifugation of blood samples at low temperature without checking platelet counts can lead to residual platelets in the processed samples, which could have affected the measurements, especially PAI-1 values.…”
Section: Discussionmentioning
confidence: 81%
“…The tPA ELISA kit does not detect t-PA associated with PAI-1; it only detects free t-PA as supported by the protocol provided along with this kit specifying that functionally active tPA will form a covalent complex with biotinylated human PAI-1, which is bound to the avidin coated on the microtiter plate, and that complexed tPA will not bind to the PAI-1 and will not be detected by the assay. The reliability of these assay reagents has been verified, and the studies quantifying soluble fibrin measured using these reagents have been published ( 19 21 ).…”
Section: Methodsmentioning
confidence: 95%
“…They activate innate immune responses, leading to inflammation and coagulation activation, which are essentially physiological responses for hemostasis and tissue repair. However, if the trauma is sufficiently severe, these responses change from physiological to pathological conditions, resulting in DIC development (12). Antithrombin (AT), a natural anticoagulant, plays an important role in the coagulation pathway by showing 80% inhibitory activity against thrombin (13).…”
Section: Introductionmentioning
confidence: 99%